Emerging investigator series: the rise of nano-enabled photothermal materials for water evaporation and clean water production by sunlight - Wang, Peng (Environmental science. Nano, 2018)
Solar driven water evaporation and distillation is an ancient technology, but has been rejuvenated by nano-enabled photothermal materials in the past 4 years. The nano-enabled state-of-the-art photothermal materials are able to harvest a full solar spectrum and convert it to heat with extremely high efficiency. Moreover, photothermal structures with heat loss management have evolved in parallel. These together have led to the steadily and significantly improved energy efficiency of solar evaporation and distillation in the past 4 years. Some unprecedented clean water production rates have been reported in small-scale and fully solar-driven devices. This frontier presents a timely and systematic review of the impressive developments in photothermal nanomaterial discovery, selection, optimization, and photothermal structural designs along with their applications especially in clean water production. The current challenges and future perspectives are provided. This article helps inspire more research efforts from environmental nano communities to push forward practical solar-driven clean water production. This frontier reviews impressive progresses of nano-enabled solar-driven water evaporation and clean water production made in the past 4 years.